Análisis e interpretación a los estados financieros de la “Cooperativa de transporte Jumandy”, de la provincia de Napo, cantón Tena; al periodo 2014 – 2015 - Yumbo Grefa, Ligia Marlene (2017)
The investigation work consisted on the Analysis and interpretation to the Financial States of the Cooperative of Transport Jumandy, of the city of Tena, county of Napo; I work that was carried out based the pertinent and outstanding theory regarding the topic and in the States very kindly proportionate Financial 2014 and 2015 for the gentleman Manager of the Cooperative of Transport Jumandy. I work that was developed with two specific objectives, in the social-institutional environment, with the purpose of introducing to the gentleman Manager of the Cooperative the Report of the Financial Analysis as tool for the taking of decisions to future; and, in the academic environment, with the purpose of opting for the grade of Ingeniera in Accounting and Audit CPA. Having the General Balance and of the State of having Been by the periods economic 2014 and 2015, the methods of horizontal and vertical analysis of the groups, subgrupos and main bills were applied, the variation percentages shown in each one of the analyzed squares being determined that they show up in the literal of results; likewise, the reasons or financial indicators settled down as: Average reason, work Capital, Index of indebtedness, Leverage or leverage, Concentration of indebtedness, Operative Yield on active and finally the Index of profitability. This whole analysis was summarized once in the Report that will surrender to the representing legal gentleman of the Cooperative, concluded the work.